Effect of measles outbreak on vaccination uptake - Thomas Schober (Johannes Kepler University Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2018)
This paper explores the effects of a measles outbreak on vaccination uptake in Austria, using administrative data with individual-level information on childhood vaccinations. I define a treatment group of children affected by the outbreak, and compare them with a control group of earlier-born children who are unaffected. Twelve months after the outbreak, the vaccination rate of the treatment group is 2.5 (first dose of the measles, mumps and rubella vaccine) and 4 (second dose) percentage points higher than the corresponding rates of the control group. The results do not indicate that families at increased risk respond more strongly, suggesting that the outbreak changed the perceived value of vaccinations across the whole population. Findings also reveal heterogeneity in the response of families based on the parents' level of education, indicating that parents with higher education levels absorb new information more rapidly.
Keywords: I12; I18; H42; H51; 330; vaccination; measles outbreak; health behaviour